COMPARATIVE EFFICACY OF BIO PESTICIDES AND INSECTICIDES AGAINST TOMATO THRIPS (THRIPS TABACI LIND.) AND THEIR IMPACT ON COCCINELLID PREDATORS - G. NAGA BHARANI,; H. KOHILAMBAL,; P. SIVASUBRAMANIAN,; G. BANUPRATHAP, (The Bioscan, 2015)
Field studies were carried out to evaluate efficacy of biopesticides viz., Beauveria bassiana (2.5 kg ha-1) and Verticilliumlecani (2.5 kg ha-1) and novel insecticides viz., Imidacloprid 30.5 SC (100mL ha-1) and Thiomithoxam 25 WG (75g.a.i. ha-1) against the thrips, Thrips tabaci Lind. and predatory coccinellids in tomato ecosystem. Significantly lowest thrips population was recorded in insecticidal treatments Imidacloprid 30.5 SC + Thiomithoxam 25 WG (1.15 nymphs plant-1) followed by Thiomithoxam 25 WG (1.35 nymphs plant-1) and Imidacloprid 30.5 SC (1.37 nymphs plant-1) compared to bio pesticides Beauveria bassiana + Verticillium lecani (2.01 nymphs plant-1) followed by Beauveria bassiana, Verticillium lecani (2.12 and 2.33 nymphs plant-1 respectively) compared to control treatment recorded 6.27 nymphs plant-1. Against coccinellids bio pesticide treatments Beauveria bassiana, Verticillium lecani (3.26 and 3.12 coccinellids plant-5 respectively) were found safer following insecticides Imidacloprid 30.5 SC and Thiomithoxam 25 WG (2.64, 2.79 coccinellids plant-5 respectively) showed lower toxic compared to control treatment (3.53 coccinellids plant-5) in tomato ecosystem. The use of bio pesticides and neonicotinoids can be used in compatible manner in future IPM programmes for controlling thrips and reducing effect on natural enemies.